Clinical application of AIMS65 score to predict outcome in patients with acute upper gastrointestinal bleeding - Maharjan, Kijan; Mandal, Rajesh Kumar; Shrestha, Sanjay (Nepal Mediciti Medical Journal, 2021)
BACKGROUND: Acute upper gastrointestinal bleeding (AUGIB) is a potentially life-threatening condition that requires rapid assessment in the emergency department. The current available scores are complex and have not been widely used in clinical practice. AIMS65 score is a simple score that can be used to risk stratify patients with AUGIB. METHODS: This was a descriptive cross-sectional study done at a single tertiary centre, NAMS, Bir Hospital among the patients presenting with AUGIB from August 2018 to January 2019. AIMS65 scores were calculated in patients presenting with acute UGIB by allotting 1 point each for albumin level < 3g/dl, INR > 1.5, alteration in mental status, systolic blood pressure ≤90 mm Hg, and age ≥65 years. Risk stratification was done during the initial 12 hours of hospital admission. RESULTS: A total of 84 patients consisting of 68 males and 16 females were enrolled in our study, with age ranging from 27 to 80 years. ICU admission, endoscopic therapy and blood transfusion were required in 22,44 and 49 patients respectively. In-patient mortality, the need for blood transfusion, endoscopic therapy or ICU admission were higher in those with AIMS65 score ≥ 2 showing statistically significant positive association (p=0.000). CONCLUSION: AIMS65 score is a simple non-endoscopic risk score that can be applied in patients of acute upper gastrointestinal bleeding to risk stratify and to predict in-patient mortality, the need for blood transfusion, endoscopic therapy or ICU admission.